A Scientometrics Analysis of The Research Productivity of Pakuan University As Evidenced In The Scopus Database From 2010 To 2024 - Jayawinangun, Roni; Priatna, Dolly; Tosida , Eneng Tita; Martha, Layung Paramesti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study examines Pakuan University's scholarly output from 2010 to 2024 using Scopus data. The investigation encompassed research productivity, trends, subject areas, publication sources, author contributions, and collaborative efforts. Pakuan University produced 685 papers, with Scopus publications showing rapid growth, with a 32.7% yearly increase. An average citation count of 3,867 per document suggests a moderate impact. Among 1,780 contributing authors, only 12 papers were single-authored, emphasising the prevalence of collaborative research. The primary research domains include Engineering, Physics and Astronomy, Environmental Sciences, Social Science, and Computer Science. Recent research has focused on topics such as in silico, sustainability, job satisfaction, and smart villages. The main publication outlets are conference proceedings and journals, notably the IOP Conference Series, AIP Conference Proceedings, International Journal of Recent Technology and Engineering, and Journal of Engineering Science and Technology. The five most productive authors are Anna Permanasari, Diana Widiastuti, Eneng Tita Tosida, Johan Iskandar and Mochamad Yunus, whilst the most influential are Anna Permanasari, Diana Widiastuti, Eneng Tita Tosida and Dolly Priatna. The Faculty of Mathematics and Natural Sciences (FMIPA) leads in contributions, followed by the postgraduate school and the faculty of engineering. Collaborative publications are predominantly from Indonesian institutions, such as the Indonesian Education University and IPB University, with international partnerships including Japan, Malaysia, and China.